Perlindungan Hukum terhadap Anak Penyandang Disabilitas sebagai Korban Kekerasan Seksual - Nadila Purnama Sari; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Children with disabilities are often the main targets to be victims of criminals, discrimination and sexual violence. The following can be seen from the increase in criminal cases against women and children with disabilities which from year to year tends to increase. The purpose of this study is to determine the legal protection of children with disabilities as victims of sexual violence and criminal sanctions against perpetrators of sexual violence against children with disabilities. The method used is a normative method along with statutory and conceptual approaches. The results of the study show that legal protection for children as victims of sexual violence is contained in article 1 paragraph (2) of Law no. 35 of 2014 concerning child protection, namely so that the child gets protection and his rights as a child. Criminal sanctions for perpetrators of sexual violence against persons with disabilities exist in positive law in Indonesia. The criminal act of rape is contained in Articles 285 to 288 of the Criminal Code. Violence against children with disabilities there is no law that specifically regulates it but in VU No. 35 of 2014 concerning Child Protection in Article 290 paragraph (1) is threatened with approximately 7 years of imprisonment.